Integrative Analysis of Sirtuins and Their Prognostic Significance in Clear Cell Renal Cell Carcinoma - Tan, Ying; Li, Bijuan; Peng, Fang; Gong, Guanghui; Li, Ning (Frontiers in Oncology, 2020)
Sirtuins, class III histone deacetylases, are involved in multiple biological processes in cancer initiation and progression. However, the diverse expression patterns and prognostic values of sirtuins in cancers have yet to be elucidated. In this study, we first evaluated the expression and prognostic values of sirtuins in multiple cancer cohorts using publicly available TCGA pan-cancer datasets. Pan-cancer survival analysis indicated that 6 out of 7 sirtuin family members were significant associated with prognosis of clear cell renal cell carcinoma (KIRC) patients. SIRT1, SIRT3, SIRT4, and SIRT5 were associated with favorable prognosis of KIRC patients, while SIRT6 and SIRT7 were associated with unfavorable prognosis. The expression levels of SIRT4 and SIRT5 in KIRC tissues were lower than that in normal tissues, while SIRT6 and SIRT7 were higher in KIRC tissues. The expression levels of SIRT1, SIRT3, SIRT5, SIRT6, and SIRT7 were significantly correlated with tumor stage and histological grade. DNA methylation may contribute to the dysregulation of sirtuins. Finally, GSEA was conducted to predict the potential functions of sirtuins in KIRC. Our results may provide novel insights for the development of sirtuins-based cancer therapy in KIRC.